Integrating Educational Technology and Digital Learning in Communicative Arabic Language Teaching at Ma’had Daarussunnah Jambi - Abdul Hamid; Sarah Mitchell (Innovative Journal of Educational Research and Insights, 2026)
This study investigates the integration of educational technology and digital learning in communicative Arabic language teaching at Ma’had Daarussunnah Jambi. Using a qualitative case study approach, the research explores how digital tools and media are utilized to enhance the teaching and learning process. Data were collected through interviews, observations, and documentation involving teachers and students. The findings reveal that the use of technology significantly improves students’ motivation, comprehension, and communicative competence. In addition, digital media provides opportunities for interactive and student-centered learning, allowing learners to engage more actively in classroom activities. However, challenges such as limited technological infrastructure, insufficient vocabulary, and varying levels of student confidence remain significant issues. The study concludes that the effective integration of technology requires adequate institutional support, teacher readiness, and a balanced combination of traditional and modern teaching methods.